Enhanced phosphorus weathering contributed to Late Miocene cooling - Yi Zhong; Zhiguo Li; Xuefa Shi; Terry Isson; Jimin Yu; Sev Kender; Zhou Liang; George E. A. Swann; Alex Pullen; Michael E. Weber; Jinlong Du; Juan C. Larrasoaña; et al. (Nature Communications)
Abstract Late Miocene climate evolution provides an opportunity to assess Earth’s climate sensitivity to carbon cycle perturbation under warmer-than-modern conditions. Despite its relevance for understanding the climate system, the driving mechanisms underlying profound climate and carbon cycle changes – including the enigmatic Late Miocene cooling from 7 to 5.4 million years ago – remain unclear. Here, we present magnetic and geochemical paleoceanographic proxies from a hydrogenetic ferromanganese crust retrieved in the northwestern Pacific Ocean. Our results indicate a striking 50% surge in deep ocean phosphorus concentrations occurred 7 – 4 million years ago, synchronous with enhanced deep ocean oxygen consumption. Employing a global biogeochemical model, we show that increased continental phosphorus weathering, without a concurrent rise in silicate weathering, contributed to the decline in atmospheric CO2 and associated cooling over the Late Miocene. This suggests a prominent decoupling of phosphorus and silicate weathering during a major carbon cycling event over the last 10 million years.